Development of a Three-Tier Diagnostic Test Instrument to Identify the Profile of Understanding the Concept of Buffer Solution - Andriani, Nafa; Loka, I Nyoman; Sofia, Baiq Fara Dwirani (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to develop a three-tier diagnostic test instrument with minimally feasible criteria to identify the profile of understanding of the concept of buffer solution material in class XII MIPA students of State Senior High School (SMAN) 3 Mataram in the 2024/2025 academic year. The type of research used is research and development (R&D) with reference to the 4D (Define, Design, Develop, Disseminate) research model. The subjects of this study were 2 lecturers of chemistry education FKIP Unram and 2 chemistry teachers for the instrument validity test and class XII MIPA students of SMA Negeri 3 Mataram for the instrument practicality test. Data analysis techniques used include expert validity tests using Aikens'V analysis, empirical validity tests were analyzed using product-moment correlation techniques, reliability tests using Alpha Cronbach techniques, and practicality tests using percentage techniques. The three-tier diagnostic test instrument that has been developed meets the criteria of very feasible based on very valid expert validity with an Aikens'V value of 0.91, valid criteria based on empirical validity with a value range of 0.265 - 0.858, categorized as high based on reliability with a value of 0.7749, and very feasible based on practicality tests with a percentage value obtained of 81% - 100%. In the concept of buffer solution material, most students experienced misconceptions, namely 64.10% compared to students who understood the concept of 24.74%, 11.07% of students did not understand the concept, and 0.69% of students guessed.